Pelatihan Dan Sosialisasi Ecoprint Pada Totebag di SDN 1 Bakalan Rayung Kudu Jombang - Sa'adah, Lailatus; Maksum, Jafar Sodiq; Maulana, Ilham; Maisaroh, Santi Fatna; Qomariyah, Siti Nur; Agustin, Zeni Aristiya (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2025)
Ecoprint is a natural coloring technique using natural materials such as leaves, flowers, and other plant parts that will be manually pounded on tote bags to produce colors with special techniques. The purpose of Ecoprint training is to utilize materials from the surrounding environment to become a profitable business. The method of conveying the theory of Ecoprint making is the offline method and the question-and-answer method. For totebag making training, demonstration, and practice methods are used. In the Ecoprint training on tote bags at SDN Bakalanrayung, class 6, an example of how Ecoprint skills can create good art, so that the price is relatively expensive. Students take part in the training with great enthusiasm and enthusiasm because this training has never been given before. The results of the Ecoprint training are quite good, to maximize it, of course, continuous training is needed so that the results are more satisfying.